KESESUAIAN PERTIMBANGAN HAKIM BANDING DALAM MEMUTUS PERKARA TINDAK PIDANA PENIPUAN DENGAN PASAL 241 KUHAP - Sari, Neiska Aulia Marcela; Kurniawan, Itok Dwi (Verstek, 2021)
This research examines the problem whether the considerations of the panel of appellate judges that giving verdict of upheld the previous court’s decision to the defendant in case number : 237/Pid/2022/PT SMG in accordance with article 241 of The Criminal Procedure Code. Based on the result of the research and discussion it was concluded that the considerations of the panel of judges of appeal who examined and decided on the case in case number : 237/Pid/2022/PT SMG were accordance with article 241 of the Criminal Procedure Code. The judges stated that they strengthened the Klaten District Court Verdict Number : 41/Pid.B/2022/PN Kln which stated that the defendant Eko Prayitno bin Nyamin had been legally and convincingly proven guilty of commiting an act of fraud joinly.Keywords: Considerations of The Panel of Judges of Appeal, Criminal Acts of Fraud, Judge’s Decision